Exploring Transition Education and Community-Based Instruction for High School Students with Disabilities: A Practice in Taiwan - Pan, Cheng-Chen (Journal of the American Academy of Special Education Professionals, 2011)
Research indicates that transition education contributes to forming a long-term support to high-school students with disabilities for their adult life. Also, Community-Based Instruction (CBI) which is a preparation of vocational skills and awareness, has its positive influences improvement of self-esteem as result of higher work inclination and employment. A car-washing curriculum of a CBI practice created an "acquisition-rich" environment" with the Scaffolding Theory in one high school located in Taiwan and brought about the mutual connection between the school and a local community. The educational implementation had yielded its benefits because of the emphasis of transition education and CBI. In this case, car-washing as a CBI facilitated student-initiated learning which promoted intellectual disabled students’ vocational skills, awareness and self-efficacy and became a critical role between a school and a community.